Electrophoretic Deposition of Hydroxyapatite: Electrophoretic deposition of hydroxyapatite - Behnamghader, Aliasghar; Bagheri, Narjes; Raissi, Babak; Forati, Tahmineh; Ntentopoulou, Dionysia; Marzbanrad, Ehsan (Iranian Journal of Pharmaceutical Sciences, 2008)
The purpose of this study was to investigate the deposition of the hydroxyapatite(HA) coating via the electrophoresis procedure. The HAdeposition was performedin an ethanol, methanol, acetone and isopropanol suspension. Methanol was foundto be the best deposition media. Among the different environmental conditions,including the encapsulation of the samples under two vacuum types of pressure(10-5-10-4and 2×10-2Torr) and also thepurge of the argon gas in the tube-likefurnace, the optimum environment was the one demonstrating the encapsulation underthe vacuum pressure of 2×10-2Torr (washing with argon gas of 99.9% purity). Afterthe examination of 3 sintering temperatures (1020, 1050 and 1100 ºC), the sinteringtemperature at 1050 ºC illustrated the most desired results. The samples sintered underthese conditions were apparently intact, most of the interfacial part of the coatingwas found to be attached to the substrate surface irregularities and no single crackswere observed.